Multikultural Adalah Kehendak Allah - Anhari, Anhari (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to explore the Islamic creed (aqidah) in understanding iradah (Allah's will) in relation to sunnatullah (Allah's decree), particularly regarding the inherently multicultural nature of human life. This research is crucial to ensure that Muslims, in particular, do not fall into